Regulation of body weight and food intake by AGRP neurons during opioid dependence and abstinence in mice - Laing, Brenton T.; Jayan, Aishwarya; Erbaugh, Lydia J.; Park, Anika S.; Wilson, Danielle J.; Aponte, Yeka (Frontiers in Neural Circuits, 2022)
Dysregulation of body weight maintenance and opioid dependence are often treated as independent disorders. Here, we assessed the effects of both acute and long-term administration of morphine with and without chemogenetic activation of agouti-related peptide (AGRP)-expressing neurons in the arcuate nucleus (ARCAGRP neurons) to elucidate whether morphine and neuronal activation affect feeding behavior and body weight. First, we characterized interactions of opioids and energy deficit in wild-type mice. We observed that opioid administration attenuated both fasting-induced refeeding and ghrelin-stimulated feeding. Moreover, antagonism of opioid receptors blocked fasting-induced refeeding behavior. Next, we interfaced chemogenetics with opioid dependence. For chemogenetic experiments of ARCAGRP neurons, we conducted a priori behavioral qualification and post-mortem FOS immunostaining verification of arcuate activation following ARCAGRP chemogenetic activation. We administered clozapine during short-term and long-term morphine administration paradigms to determine the effects of dependence on food intake and body weight. We found that morphine occluded feeding behavior characteristic of chemogenetic activation of ARCAGRP neurons. Notably, activation of ARCAGRP neurons attenuated opioid-induced weight loss but did not evoke weight gain during opioid dependence. Consistent with these findings, we observed that morphine administration did not block fasting-induced activation of the ARC. Together, these results highlight the strength of opioidergic effects on body weight maintenance and demonstrate the utility of ARCAGRP neuron manipulations as a lever to influence energy balance throughout the development of opioid dependence.